Determination of Blood Glucose, Total Protein, Certain Minerals, and Triiodothyronine during Late Pregnancy and Postpartum Periods in Crossbred Dairy Cows - Shima Essameldin Mohammed; Faisal Omer Ahmad; Ehab A. M. Frah; Imadeldin Elfaki (Veterinary Medicine International)
The late pregnancy (3rd trimester) and the postpartum period (PPP) (calving date or day zero to day 45) are very critical periods for the fertility and production in dairy cows. This study was designed to investigate blood glucose, total protein (TP), calcium (Ca), phosphorus (P), magnesium (Mg), iron (Fe), and triiodothyronine (T3) during late pregnancy and the PPP. Twenty-seven apparently healthy multiparous crossbred dairy cows (Friesian × Kenana) were included in this study. The cows were randomly allocated into three groups: group A (n = 10), cows with late pregnancy, group B (n = 7), cows in the PPP, and group C (n = 10), nonpregnant cows as control. One-way ANOVA was used to analyze the data. The results of this study showed that blood glucose was higher in late pregnancy and the PPP than in nonpregnant cows. The TP was significantly lower in late pregnant cows than during the PPP and in nonpregnant cows. Ca, P, and Mg were not significantly different between periods. Serum Fe and T3 were significantly lower during the PPP than that in late pregnant and nonpregnant cows. The results can provide indications of the nutritional status of dairy cows and a diagnostic tool to avoid the metabolic disorders that may occur during late pregnancy and the PPP.